(untitled) (Journal of Human Sciences, 2023)
Applied linguistics is a linguistic science that appeared in the middle of the twentieth century, and it is a science that invests the results of different knowledge and sciences, and the field of this science is language education. Foreign language education. In its theoretical aspect, this research provides a brief overview of the emergence of applied linguistics, highlighting the most important points related to what is known as language teaching. As for the applied aspect of this research, it is devoted to the Arabic language book for the first grade of basic education scheduled in the State of Libya. It provides a general description of the book, then It presents a presentation of its contents, highlighting some aspects of applied linguistics that the authors of the book adhered to. The research came in an introduction, two chapters and a conclusion. Dictionaries, and talking about the role of translation towards dictionaries, and the role of dictionaries towards translation, then the conclusion of the research including the most important results reached by the researcher, mentioning references and comments at the end of the research, followed by mentioning sources and references.